2015
DOI: 10.1159/000438789
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Progesterone in MPTP-Treated Male Mice

Abstract: Background: Numerous studies have reported on the neuroprotective activity of estradiol, whereas the effect of the other ovarian steroid, progesterone, is much less documented. Methods: This study sought to investigate neuroprotection with a low dose of progesterone (1 µg) in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated male mice to model Parkinson's disease and compare it to the effect of this steroid in intact mice (experiment 1). We also investigated if high doses of progesterone could protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 66 publications
(81 reference statements)
3
26
0
1
Order By: Relevance
“…After treatment, the mice were killed, and the intestines collected. The doses of progesterone administered in the present study were previously shown to be neuroprotective against MPTP in the brains of mice in our previous publications . The rationale for testing the effect of progesterone in the gut is that we previously reported neuroprotection in the brain with progesterone .…”
Section: Methodsmentioning
confidence: 75%
See 4 more Smart Citations
“…After treatment, the mice were killed, and the intestines collected. The doses of progesterone administered in the present study were previously shown to be neuroprotective against MPTP in the brains of mice in our previous publications . The rationale for testing the effect of progesterone in the gut is that we previously reported neuroprotection in the brain with progesterone .…”
Section: Methodsmentioning
confidence: 75%
“…The Laval University Animal Care Committee approved the animal studies. All efforts were made to minimise animal suffering and to reduce the number of mice used . The experiment planned 10 mice per group and, if available, an additional mouse was added to a group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations